Penggunaan organic priming dan periode inkubasi untuk invigorasi benih cabai merah (Capsicum annum L.) kadaluarsa pada stadia perkecambahan - Halimursyadah Halimursyadah; Jumini Jumini; Muthiah Muthiah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
Using Organic Priming and Incubation Period for Invigoration of Chilli Seed Expired at Germination Stage ABSTRACT. The purpose of this study was to determine the effect of organic priming and incubation period to increase viability and vigor of expired chilli seeds and interaction between of two factors. This research was conducted in the Laboratory of Seed Science and Technology Faculty of Agriculture, Syiah Kuala University in Banda Aceh, from March until November 2012. Using completely randomized design (CRD) factorial, the first factor is organic priming (banana extract and coconut water) and the second factor is incubation period (24, 48, 72 hours). The results showed that interaction between types of organic priming and incubation period significan affect to increase viability and vigor of expired chilli seeds, especially on potential growth, germination, speed of germination, first count germination and T50. The best treatment showed by using coconut water and 48 hours incubation periods.